PELAKSANAAN MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 4 PEUSANGANKABUPATEN BIREUEN - Musbir Musbir (Jurnal Ilmiah Didaktika, 2014)
School based management (MBS) is an alternative in educational management that emphasizes in the school autonomy and creativity to improve the quality of education. This research is aiming at knowing the implementation of MBS in the field of: 1) learning teaching process, 2) school administration, and 3) school relationship with society to improve the quality of SMPN 4 Peusangan Bireuen Regency. This research used a qualitative approach with a descriptive method. The data were gathered by using observation, interview and documentation. The subject of the research were school principal, vice principal, teacher, and school’s committee. The result showed as follow:1) In learning teaching process, there were three activities, they were: a) opening; checking attendance, asking previous material (pretest) and apperception, b) main activity; explaining about aims of study, writing the core of materials, explaining the materials, using instructional tools and concluding the study, and c) closing; giving question,reexplaining unclear material, giving assignment (posttest), and informing the materials that will be discussed in the next meeting. 2) for school’s personnel,there were supervising and developing the school’s personnels by involving them in making decision of the school, activating the school’s MGMP, sending teachers to follow trainings, giving permittion for teachers who want to pursue their degree. Besides, there were also promotion, mutation, job discontinuance,compensation and employees’ evaluation. 3) to build school relationship with the society, there were several efforts have been done such as forming and empowering school’s committee, having a routine meeting with school’s committtee at the end of semester, obligating the parents to take the rapport of their children every semester, explaining the improvement and the declining of school’s prestige,building the relationship with society to be involved actively in the improvement of educational quality, providing information about the school to the society and cultivate the transparancy in school management.